Kompetensi dan Integritas Meningkatkan Kinerja Pegawai dalam Penyusunan Laporan Penyelenggaraan Pemerintah Daerah (LPPD) Kota Palembang - Agustianingsih, Dwi; Hidayat, Bachtari Alam; Agus, Azwar (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2025)
The purpose of this study is to analyse the effect of employee competence and integrity on employee performance in the preparation of LPPD in Palembang City. Independent variables are competence (X1), and integrity (X2), while the dependent variable is employee performance (Y). Respondents of this study amounted to 78 people. Data collection was carried out by giving a questionnaire consisting of 28 statement items to respondents with answers based on the 1-4 scale rating system. Data were analysed using multiple linear regression with the help of SPSS 25. Employee competence and employee integrity have a positive and significant influence on employee performance in preparing LPPD in Palembang City partially and simultaneously. Competence is indicated by employees having sufficient motivation, character, self-awareness, knowledge, and skills to carry out their tasks effectively. Meanwhile, integrity serves as a strong ethical and moral foundation, enabling employees to work with loyalty, responsibility, commitment, and care. Some recommendations to improve employee performance include the development of ongoing training programs that focus on improving technical skills; the implementation of a performance evaluation system that measures work results as well as integrity and commitment; the strengthening of internal oversight mechanisms; and the enhancement of stakeholder involvement in the preparation and evaluation of the LPPD to ensure government accountability and transparency.